Rapid conventional scheme for biochemical identification of antibiotic resistant enterobacteriaceae isolates from urine. Issue 9 (September 1988) - Perry, J D; Ford, M; Hjersing, N; Gould, F K
Abstract : Six conventional biochemical tests were combined to produce an identification scheme. These tests included decarboxylation of lysine and ornithine, fermentation of glucose and cellobiose, indole production and urease production. Three hundred antibiotic resistant coliforms from urine specimens were tested by this scheme and also by the API 20E for comparison. Two hundred and seventy nine (93%) of organisms were correctly identified using the six tests, 17 (5.7%) were referred for further study, and four (1.3%) were misidentified. It is concluded that this combination of tests provides an inexpensive, accurate, and rapid tool for identification.